2017
DOI: 10.1016/j.euromechflu.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuity of lift on a hydrofoil in reversed flow for tidal turbine application

Abstract: h i g h l i g h t s • Measurement of forces on a NACA0015 hydrofoil in reverse flow : sharp leading edge, rounded trailing edge. • Strong discontinuity of lift with hysteresis is observed around 0°angle of attack. • Leading edge separation on suction side triggers transition. • Turbulent suction side boundary layer separates farther on rounded trailing edge than on laminar pressure side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…The complexity of the problem here arises from rotational motion and the coupling of structural and aerodynamic properties, which depend on the disc shape. Moreover, these dependencies are nonlinear and can have discontinuities, as demonstrated by Marchand et al (2017).…”
Section: Cfd-based Shape Optimizationmentioning
confidence: 99%
“…The complexity of the problem here arises from rotational motion and the coupling of structural and aerodynamic properties, which depend on the disc shape. Moreover, these dependencies are nonlinear and can have discontinuities, as demonstrated by Marchand et al (2017).…”
Section: Cfd-based Shape Optimizationmentioning
confidence: 99%
“…When given to the Reynolds number effect, it is observed that the thin foil is not sensitive to the increase of Reynolds number compared with the thick foil and the blade loads would decrease as the Reynolds number increases in a specific range of the attack angle [34][35]. Marchand et al [36] observed that the occurrence of lift discontinuity is at 0 ° for the hydrofoil in reverse flow, as a consequence of the leading edge separation bubble and asymmetrical boundary layers, which can't be detected by the original RANS turbulence model. With the consideration of dynamic stall in reverse flow, the distinctive vortex structures are reverse flow dynamic stall vortices (RFDSVs) and the dynamic stall has a close correlation with the Reynolds number, pitching frequency, mean pitch angle and pitch amplitude [37], yaw angle [38] and foil shape [39].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of Reynolds number is also studied by Lind et al [12] for NACA0012 and NACA0024 airfoils and it concludes that the airloads of NACA0012 is almost insensitive to the Reynolds number compared with NACA0024, for the reason that it acts like a thin airfoil because of the sharp leading edge. At incidence of 0 °, Marchand et al [13] found that the discontinuity lift occurs for NACA0015 hydrofoil at Reynolds number of 5×10 5 , which is induced by the leading-edge separation bubble and asymmetrical boundary layer near the blunt trailing edge. When it comes to the reversed pitching airfoil, Lind and Jones [14] reported that the reversed dynamic stall is weakly sensitive to the Reynolds number, but is strongly affected by the reduced frequency.…”
Section: Effect Of Time-varying Freestream On Performance and Vortex ...mentioning
confidence: 99%